Near-wall treatment for the simulation of turbulent flow by the cumulant lattice Boltzmann method. (1st January 2020) - Pasquali, Andrea; Geier, Martin; Krafczyk, Manfred
Abstract: We present a new wall function implementation for the cumulant lattice Boltzmann method that sets a partial slip velocity on the wall by computing a skin frictional coefficient. Our approach uses local information and is particularly appropriate for implementations on general purpose graphics processing units. The validation of the model has been conducted by performing numerical simulations of the turbulent channel flow test case with different grid resolutions and for different Reynolds numbers. The results showed encouraging agreement with Direct Numerical Simulation data for velocity profile, Reynolds shear and normal stresses.